Efficacy and safety of Xa inhibitors for the treatment of cancer-associated venous thromboembolism. Issue 4 (3rd April 2019) - Kimpton, Miriam; Carrier, Marc
ABSTRACT: Introduction : Cancer patients with cancer-associated thrombosis (CAT) are at an elevated risk of recurrent venous thromboembolism (VTE) and of major bleeding while receiving treatment with anticoagulation. Recently, Xa inhibitors have been assessed in cancer patients for the treatment of CAT, providing clinicians and patients with more treatment options. Areas covered : In this narrative review, the authors evaluate the evidence regarding the efficacy and safety of edoxaban, rivaroxaban, and apixaban in the treatment of CAT. Expert opinion : Xa inhibitors are an effective, safe, and convenient option for the treatment of CAT. Overall, they may be associated with a lower risk of recurrent VTE in cancer patients. Certain subgroups of cancer patients may be at increased risk of major bleeding while on treatment with Xa inhibitors, when compared to low-molecular-weight-heparin (LMWH). The current published data suggests an increase in gastrointestinal (GI) major bleeding in patients with GI malignancies. Other patient, treatment, and cancer characteristics may also be associated with a higher risk of major bleeding. Therefore, when assessing the appropriateness of Xa inhibitors for the treatment of CAT, the clinician must take into consideration the known interactions of these drugs, the individualized bleeding risk, and the patient's preferences, in order to make the best possible anticoagulation therapy recommendation.